2007
DOI: 10.1128/jcm.01244-07
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a PCR-Oligochromatography Test for Detection of Trypanozoon Parasites in a Multicenter Collaborative Trial

Abstract: A PCR-oligochromatography test for diagnosis of human and animal trypanosomiasis was evaluated through a multicenter ring trial with six laboratories testing a set of 21 blinded samples, resulting in qualitative data (positive or negative). Results showed an intralaboratory repeatability (accordance) of 88.7% (credible interval [CI], 84.4 to 92.5%) and an interlaboratory repeatability (concordance) of 88.1% (CI, 84.3 to 92.3%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…All discrepancies were caused by failed detection in one of two runs at PAMM resulting from possible low loads of enterovirus or due to incidents of contamination. The values for accordance and concordance that were found in our study are higher or at least in the same range as those reported in other multicenter evaluations of molecular tests (3,4).…”
supporting
confidence: 77%
“…All discrepancies were caused by failed detection in one of two runs at PAMM resulting from possible low loads of enterovirus or due to incidents of contamination. The values for accordance and concordance that were found in our study are higher or at least in the same range as those reported in other multicenter evaluations of molecular tests (3,4).…”
supporting
confidence: 77%
“…To our knowledge, this is the first study evaluating the ACC and CON of molecular diagnostic tests for human African trypanosomiasis and leishmaniasis on blood samples. The ACC and CON of the Tryp‐PCR‐OC have already been estimated in a multicentre ring trial with six participating laboratories on purified DNA specimens, reported by Claes et al. (2007).…”
Section: Discussionmentioning
confidence: 99%
“…While PCR with RFLP requires about 3 h for analysis of the reaction product and determination of the parasite species of positive samples, RLB takes Ͻ2 h. In addition, it should be possible to further simplify RLB by using PCR-oligochromatography and developing dipsticks, similar to those used to detect animal and human trypanosomes or toxoplasmosis, where detection can be obtained within 5 min of completion of the PCR. This would further simplify the analysis of CL samples (6,10).…”
Section: Discussionmentioning
confidence: 99%